2017
DOI: 10.4236/jssm.2017.106038
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Burnout, and Emotional Labor Correlation among Teachers in Pakistan

Abstract: The main purpose of this research is to study the impact of personality on job burnout among educators. Additionally the role of emotional labor on the relationship of personality and burnout is also investigated. In this model, job burnout (exhaustion, depersonalization and lack of personal accomplishment) is a dependent variable; personality (extraversion, neuroticism, agreeableness, openness to experience and conscientiousness) is an independent variable, while emotional labor (surface acting and deep actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…Nevertheless, whether burnout is the result of emotional labor or burned-out employees start to employ surface acting responses as they lack the resources to apply more genuine and empathetic strategies (i.e., deep and natural acting) is not yet well understood. Few studies have examined burnout as the cause of emotional labor [ 8 , 15 , 36 ], and those that did have shown that burnout leads to greater surface acting strategies and emotional labor. This association is consistent among the studies, suggesting that when emotional exhaustion and fatigue rises, surface acting rises too [ 16 , 33 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, whether burnout is the result of emotional labor or burned-out employees start to employ surface acting responses as they lack the resources to apply more genuine and empathetic strategies (i.e., deep and natural acting) is not yet well understood. Few studies have examined burnout as the cause of emotional labor [ 8 , 15 , 36 ], and those that did have shown that burnout leads to greater surface acting strategies and emotional labor. This association is consistent among the studies, suggesting that when emotional exhaustion and fatigue rises, surface acting rises too [ 16 , 33 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the studies that examined burnout as a predictor of emotional labor, they indicate that greater exhaustion scores predict emotional labor [ 8 ]. Correspondingly, further studies also show that higher burnout levels are related to higher surface acting while lower burnout levels are related to NFE; no associations were observed between burnout and deep acting [ 15 , 36 ].…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a known fact that the teaching profession requires high levels of efforts and, therefore, professionals working in education are known to be susceptible to burnout (Chang, 2009). Considering different types of goal orientations, in their efforts to be effective teachers with mastery goal orientations are expected to try hard, do research, learn and develop themselves and carry out activities that require effort and also support students in the learning process.…”
Section: -1617mentioning
confidence: 99%